Is Innervation of the Neuromuscular Junction at the Diaphragm Modulated by sGC/cGMP Signaling? - Lukáčová, Nadežda; Hricová, L’udmila; Kisucká, Alexandra; Papcunová, Štefánia; Bimbová, Katarína; Bačová, Mária; Pavel, Jaroslav; Marsala, Martin; Vanický, Ivo; Dzurjašková, Zuzana; Matéffy, Stanislav; Lukáčová, Viktória; et al. (Frontiers in Physiology, 2020)
We previously reported NO/sGC signaling in the upper respiratory pathway, receiving input from the respiratory neurons of the brainstem to phrenic motoneurons in the C3–C6 spinal cord. In order to assess whether innervation of the neuromuscular junction (NMJ) at the diaphragm is modulated by sGC/cGMP signaling, we performed unilateral eight-day continuous ligation of the phrenic nerve in rats. We examined sGCβ1 within the lower bulbospinal pathway (phrenic motoneurons, phrenic nerves and NMJs at the diaphragm) and the cGMP level in the contra- and ipsilateral hemidiaphragm. Additionally, we characterized the extent of phrenic nerve axonal degeneration and denervation at diaphragm NMJs. The results of our study show that continuous eight-day phrenic nerve ligation caused a marked increase in sGCβ1 (immunoreactivity and the protein level) in the ipsilateral phrenic motor pool. However, the protein sGCβ1 level in the phrenic nerve below its ligation and the cGMP level in the ipsilateral hemidiaphragm were evidently decreased. Using confocal analysis we discovered a reduction in sGCβ1-IR boutons/synaptic vesicles at the ipsilateral MNJs. These findings are consistent with the marked axonal loss ( 47%) and significant NMJs degeneration in the ipsilateral diaphragm muscle. The remarkable unilateral decrease in cGMP level in the diaphragm and the failure of EMG recordings in the ipsilateral hemidiaphragm muscle can be attributed to the fact that sGC is involved in transmitter release at the diaphragm NMJs via the sGC-cGMP pathway.